Competition between the impact of cation distribution and crystallite size on properties of MnxFe3−xO4 nanoparticles synthesized at room temperature. Issue 17 (1st December 2017) - Modaresi, Nahid; Afzalzadeh, Reza; Aslibeiki, Bagher; Kameli, Parviz
Abstract: In the present study, the effect of Mn doping on the structural, morphological and magnetic properties of Mnx Fe3−x O4 (0≤x≤1) samples has been investigated. The obtained X-ray diffraction patterns indicate that the crystallite size depends on the cation distribution in the samples. The Rietveld full-pattern fitting by MAUD software determines the cation distribution, ion coordination, ion occupancy, crystallite size, microstrain and unit cell parameter. The magnetic hysteresis measurements show that the saturation magnetization and effective anisotropy constant decrease by increasing the Mn content up to x=0.2, while they increase by further Mn doping. Structural and magnetic properties have been completely described on the basis of the competition between the effects of cation distribution and crystallite size. The obtained results show an increase in the crystallite size and consequently, increase in magnetization for the 0.2<x≤0.5 samples. The near-zero Hc value and also, the peak temperature of AC susceptibility TB < 300 K in the 0≤x≤0.2 samples confirm superparamagnetic behavior of these samples at room temperature. The AC susceptibility results show the presence of strong interparticle interactions. Furthermore, the application of the samples in magnetic hyperthermia has been investigated. It has been found that the sensitivity of the nanoparticles to the variations of applied frequencies, being an important parameter in the hyperthermia method, is enhanced by Mn doping in the Fe3 O4 samples.